Morphological and molecular evidence for a new species of freshwater crab of the genus Sudanonautes Bott, 1955 (Brachyura: Potamoidea: Potamonautidae) from Cameroon, with notes on its ecology - Ndongo, Pierre A. Mvogo; Schubart, Christoph D.; Rintelen, Thomas Von; Tamesse, Joseph L.; Cumberlidge, Neil (Zootaxa, 2017)
A new species of freshwater crab of the genus Sudanonautes Bott, 1955, is described from the tropical rainforests of Edea and Tiko in southern Cameroon, Central Africa. Sudanonautes tiko n. sp. is recognized by a unique combination of characters of the carapace, thoracic sternum, chelipeds, and male first gonopod, and by distinct mtDNA sequences for two loci (COI and 16S rRNA). A diagnosis, illustrations, and a tree of phylogenetic relationships based on mtDNA sequences are provided, along with a comparison to similar species from the region. Brief notes are provided on the ecology of the new species and of three other species of Sudanonautes collected during this study.